Clinical and Laboratory Profile of Children with Eosinophilia at Dhulikhel Hospital - Shrestha, S; Singh, S Dongol; Shrestha, NC; Shrestha, RPB (Kathmandu University Medical Journal, 2013)
Background Eosinophilia in children is commonly caused by or parasitic, allergic and immunologic problems. Objectives To study clinical and laboratory profile of patients with eosinophilia and to identify possible causes. Method A prospective and descriptive study was conducted from January 2009- December 2011. All the cases of eosinophilia with symptoms and signs of single or multiple organ were included. The known caused of eosinophilia like allergy, asthma and drugs were excluded. Results During three years period, 84(2.41%) cases had eosinophilia with single or multiple organ involment. 14.3%, 39.3% and 46.4% had mild, moderate and severe eosinophilia respectively, with cases of hypereosinophilia comprising 85.7%. Eosinophilia is seen predominantly in tamang caste with overall age ranging from 1-14 years. Most common symptoms and signs are abdominal pain (67.9%) hepatomegaly (59.5%) respectively. Gastrointestinal system was most commonly involved organ followed by respiratory system. Nineteen percent had polyserositis involving pleural, pericardial effusion and ascites at presentation. Out of 84 patients only nine serum samples were able to be sent for parasitological analysis. sixteen had identifiable and/ or possible causes. Serum sample for parasitological analysis revealed fascilosis, filariasis, strongylosis stercoralis and toxocariasis. Conclusion Eosinophilia is more common among tamang poulation in our study. Most common symptoms and signs are abdominal pain and hepatomegaly respectively. Parasitic infection seems to be the most common cause however further study has to be done to reach final conclusion. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 58-62 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7346